2013
DOI: 10.6061/clinics/2013(08)11
|View full text |Cite
|
Sign up to set email alerts
|

Colonization pressure as a risk factor for colonization by multiresistant Acinetobacter spp and carbapenem-resistant Pseudomonas aeruginosa in an intensive care unit

Abstract: OBJECTIVE:To determine factors associated with colonization by carbapenem-resistant Pseudomonas aeruginosa and multiresistant Acinetobacter spp.METHODS:Surveillance cultures were collected from patients admitted to the intensive care unit at admission, on the third day after admission and weekly until discharge. The outcome was colonization by these pathogens. Two interventions were implemented: education and the introduction of alcohol rubs. Compliance with hand hygiene, colonization pressure, colonization at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
0
22
0
3
Order By: Relevance
“…En la presente investigación se logró determinar además que el estado portador en pacientes fue más frecuente en hombres con un 68,4%, observándose además que el 42,1% de ellos presentaron un rango de edad de 58-77 años, la frecuencia de mayor colonización en el género masculino también ha sido (29) reportada en otras investigaciones similares ; dejando abierto el debate del porque se suscita este evento.…”
Section: Resultsunclassified
“…En la presente investigación se logró determinar además que el estado portador en pacientes fue más frecuente en hombres con un 68,4%, observándose además que el 42,1% de ellos presentaron un rango de edad de 58-77 años, la frecuencia de mayor colonización en el género masculino también ha sido (29) reportada en otras investigaciones similares ; dejando abierto el debate del porque se suscita este evento.…”
Section: Resultsunclassified
“…The literature search identified a total of 165 citations; of which, 98 full-text articles were retrieved and assessed for eligibility. The systematic review included 19 articles (6 articles for AIAT versus IIAT [12][13][14][15][16][17]; 17 articles for acquisition of resistant or multidrug-resistant P. aeruginosa [12,[14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30] and 4 articles reported both outcomes [12,[14][15][16]) that met final eligibility criteria ( Fig. 1).…”
Section: Baseline Study and Population Characteristicsmentioning
confidence: 99%
“…Nineteen studies reported in 17 articles (two articles contributed to four studies) were included (Table 3) [12,[14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30]. A total of 3203 total subjects (1077 cases and 2126 controls) were examined for risk factors of acquisition of [29]).…”
Section: Risk Factors For Acquiring Resistant P Aeruginosamentioning
confidence: 99%
“…As a result, colonization pressure increased due to the increase in patients already colonized upon admission. The authors concluded that when this pressure reaches critical levels, efforts aimed primarily at hand hygiene may not be sufficient to prevent transmission (27) .…”
Section: Introductionmentioning
confidence: 99%